The mental health needs and concerns of older people who identify as LGBTQ+: A narrative review of the international evidence - Mc Cann, Edward (My University, 2019)
Aims: To synthesize the best available evidence on the experiences and perceptions of older people who identify as LGBTQ+ regarding their mental health needs and concerns. Design: A narrative review and critical appraisal of qualitative, quantitative and mixed methods studies. Data sources: A systematic search was undertaken across all of the databases including PsycINFO, MEDLINE, CINAHL and Sociological Abstracts. International studies published in academic journals in the English language, from January 1995 to January 2019 were appraised. Studies had to involve older people identifying as LGBTQ+and who had experiences mental health issues. Review Methods: A total of 14 papers were selected for inclusion in the systematic review. A narrative analysis of the papers was used by synthesizing the key findings and organizing them into themes and concepts. Results: Following analysis of the data, the themes that emerged were: (i) LGBTQ+identity issues (ii) risk and vulnerability factors, (iii) coping strategies and resilience, (iv) interventions and supports. Conclusion: This review highlights key mental health-related issues that need to be taken into account in the creation and provision of appropriate, responsive and inclusive supports and services.
PUBLISHED
Keywords: Lesbian; Gay; Bisexual; Transgender; Questioning; Older people; Seniors; Aging; Mental health; Nursing; Identities in Transformation; Inclusive Society